Alternative method of maize grain quality maintenance for small farmers through hermetic storage (Research, Society and Development, 2022)
In many countries, small corn producers generally have technological limitations during storage. hermetic storage with use of PET bottles stands out as an alternative. The objective of this study was to evaluate the hermetic storage of corn in polyethylene silo bags and PET bottles as an alternative for small producers. Maize grains were stored in polyethylene silo bags, polyethylene terephthalate (PET) bottles and glass recipients for 0, 15, 30, 45, and 60 days. Were used four repetitions for each treatment. Were evaluated the traits: infestation by insect pests (%); water content (% bu.); bulk density (kg 100 L-1); electrical conductivity (µS cm-1 g-1); percentage of germination (%). The insect species that infested the corn kernels under hermetic and non-hermetic conditions was only Sitophilus zeamais. PET bottles presented the lowest percentage of infestation among the storage containers, followed by silo bags, both presented the maximum percentages of 0.65% and 30%, respectively. Water content, bulk density, electrical conductivity e percentage of germination of the maize were preserved in both hermetic storage systems that were tested for 60 days. The use of PET bottles control S. zeamais and preserve the quality of maize for at least 60 days of storage. Our study concludes that hermetic storage in PET bottles can be particularly useful and important for small farmers.